2022
DOI: 10.1021/acssensors.2c01563
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive Small-Molecule Fluorescent Thermometer Reveals Hot Mitochondria in Surgically Resected Human Tumors

Abstract: The Warburg effect suggests that upregulated glycolysis arising from high glucose uptake in cancer cells might be accompanied with suppressed mitochondrial respiration. However, recent studies have shown that the mitochondrial temperature in cancer cells could be relatively higher than that in normal cells, suggesting hyperactive mitochondrial respiration in cancer cells. However, hot mitochondria have not been reported in patients with cancer. Here, near-infrared small-molecule fluorescent probes TRNs are rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…8). 80 The probe demonstrated high sensitivity and NIR emission (600–670 nm). The fluorescence intensity at 660 nm was increased by approximately 28-fold as the temperature decreased from 60 °C to 25 °C (Fig.…”
Section: Fluorescent Thermometry Of Mitochondriamentioning
confidence: 99%
“…8). 80 The probe demonstrated high sensitivity and NIR emission (600–670 nm). The fluorescence intensity at 660 nm was increased by approximately 28-fold as the temperature decreased from 60 °C to 25 °C (Fig.…”
Section: Fluorescent Thermometry Of Mitochondriamentioning
confidence: 99%
“…Mitochondrial temperature plays a vital role in cells and tissues, and recent studies suggest that cancer cells have relatively hot mitochondria, which indicates that the active respire of mitochondria in cancer cells [10,113]. Chang et al have reported a small molecule mitochondria-targeted fluorescent probe (Mito 22 hermos yellow) with rosamine structure for monitoring temperature changes in mitochondria [114].…”
Section: Organic Probes For Mitochondrial Temperaturementioning
confidence: 99%
“…The physiological process, such as enzyme-based catalysis and 2 of 30 lipid composition, is closely associated with polarity [8,9]. Finally, various physiological and pathological states are in company with the variation of temperatures, so the temperature could reflect the state of cells and tissues [10,11]. Conspicuously, the microenvironment is of vital importance to biological organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, uorescent imaging has garnered notable interest owing to its capability for relatively straightforward operation, high sensitivity, and real-time visualization. [18][19][20][21] Therefore, the detection of intracellular viscosity with the aid of a uorescence spectrometer may become a new-established method, potentially being used for HIRI early diagnosis. To date, considerable and outstanding results have been achieved in imaging viscosity alteration in vivo.…”
mentioning
confidence: 99%